2015
DOI: 10.1111/acer.12802
|View full text |Cite
|
Sign up to set email alerts
|

Poorer Drinking Outcomes with Citalopram Treatment for Alcohol Dependence: A Randomized, Double‐Blind, Placebo‐Controlled Trial

Abstract: This trial does not support the use of citalopram in the treatment of alcohol dependence. The results suggest that the use of SSRIs among depressed and nondepressed alcohol-dependent individuals early in recovery, prior to the onset of abstinence, may be contraindicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 46 publications
0
17
0
8
Order By: Relevance
“…Furthermore, there are data from the transplant field that alcohol abstinence and recidivism rates are unchanged, with as many as 25% of waitlisted patients with alcohol-induced liver disease continuing to drinking while waitlisted. 32,33 Lastly, there have been other failed clinical trials for medications such as selective serotonin reuptake inhibitors (i.e., citalopram) to help with alcohol abstinence, 34 which all together would suggest changes in waitlisting for ALD reflect selection criteria for waitlisting rather than changes in abstinence rates for ALD.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are data from the transplant field that alcohol abstinence and recidivism rates are unchanged, with as many as 25% of waitlisted patients with alcohol-induced liver disease continuing to drinking while waitlisted. 32,33 Lastly, there have been other failed clinical trials for medications such as selective serotonin reuptake inhibitors (i.e., citalopram) to help with alcohol abstinence, 34 which all together would suggest changes in waitlisting for ALD reflect selection criteria for waitlisting rather than changes in abstinence rates for ALD.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies reported that the presence of personality disorder was associated with a significantly shorter time to first relapse. 36,38,43 In a further study that examined time to readmission in a sample of male veterans, the presence of ASPD was not a significant predictor of readmission for alcohol-related problems. 22…”
Section: Resultsmentioning
confidence: 91%
“…Doxylamine is an anti-histamine. There appears to be an increased risk of birth defects on serotonin reuptake inhibiting antihistamines, such as doxylamine, compared to non-serotonin reuptake inhibiting antihistamines [116] and similarly an increase in risk on serotonin reuptake inhibiting antidepressants, not found in antidepressants that are inactive on the serotonin system [53,117].…”
Section: Discussionmentioning
confidence: 99%